(NsOWREMENNOE NAZEMNOE OLEDENENIE SOWETSKOJ aRKTIKI (B/s - (NgOWORUHA(B, (NlEONID sERGEEWI^s ((NlENINGRAD (B:s (NgIDROMETEOIZDAT(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 237-256 (488 (NNAZW(B.)s
(NbIBLIOGR(B.: (NS(B. 237-256s
(NaRKTI^ESKIJ I aNTARKTI^ESKIJ niis
Keywords: (NlEDNIKI (B((NGEOL(B.)s -- (NaRKTIKAs